2018
DOI: 10.7809/b-e.00325
|View full text |Cite
|
Sign up to set email alerts
|

Quality of wild herbaceous legumes and its role in livestock nutrition

Abstract: Climate change in southern Africa is predicted to be severe, and animal agriculture will suff er the most. However, there exist wild legumes that have survived under harsh environmental conditions and contribute to a varied diet for the grazing ungulates. This study tested the chemical composition of four wild herbaceous legumes each from Tswapong and Ngamiland districts in Botswana (Chamaecrista abscus, Chamaecrista rotundifolia, Crotalaria sphaerocarpa, Tephrosia lupinifolia, Tephrosia purpurea, Indigofera s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Castro-Montoya et al [58] demonstrated that legume crop residues improve dry matter intake in dairy cattle than sorghum silage when fed in total mix ration. Legume forages have a higher nutritive value when compared to grasses especially during the dry season [59,60]. In semiarid environments, seasonal-constant changes in the nutritional quality of natural pastures compromise livestock quality and lead to the inclusion of leguminous plants as supplements [61].…”
Section: Fodder Nutritive Value Of Husk Leaf and Stem Plantmentioning
confidence: 99%
“…Castro-Montoya et al [58] demonstrated that legume crop residues improve dry matter intake in dairy cattle than sorghum silage when fed in total mix ration. Legume forages have a higher nutritive value when compared to grasses especially during the dry season [59,60]. In semiarid environments, seasonal-constant changes in the nutritional quality of natural pastures compromise livestock quality and lead to the inclusion of leguminous plants as supplements [61].…”
Section: Fodder Nutritive Value Of Husk Leaf and Stem Plantmentioning
confidence: 99%
“…This process might be benefi cial as non-organic nitrogen from urea is already transferred into amino acids by the rumen microbes. The amino acids can be used by the ruminant to form body´s own protein, instead of building amino acids by themselves in the fi rst step (see also Madibela et al, 2018).…”
Section: Proteinmentioning
confidence: 99%
“…These contradictions between positive and negative eff ects might be explained by the diff erences in chemical structure as the term "tannins" describes a large group of diff erent substances and every plant species has its own composition. More information about tannins is given in Madibela et al (2018).…”
Section: Plant Secondary Metabolites (Psms)mentioning
confidence: 99%
“…However, small shrubs and herbs, such as Monechma genistifolium and diff erent wild legumes, often serve as food for wild herbivores. They can also be an additional, supplementary, alternative food resource for livestock, for example in the dry season when food availability is restricted (Madibela et al, 2018). Their utilisation by herbivores, as well as their general nutritional quality, is poorly known.…”
Section: Biodiversity Chemical Diversity Resource Availability Andmentioning
confidence: 99%